Continuum many maximal consistent normal bimodal logics with inverses - Williamson, T (Duke University Press, 1998)
The paper considers extensions of a normal bimodal logic KL in which the two necessity operators are mutual one-sided inverses. A continuum of maximal consistent normal extensions of KL is constructed, each of which has infinitely many quasi-normal Post complete extensions. Some syntactic properties of maximal consistent normal bimodal logics and in particular of such extentions of KL are investigated.